Financial and non-financial factors are important indicators to evaluate performance of corporation. The main objective of this study is to build a model for improving performance of estate and plant by using balance scorecard. The study uses balance scorecard, and fuzzy analytical hierarchy process to model the criteria of performance measurement for both estate and plant. Results generated from the model of estate performance criteria measurements are seed, fertilizing, cost management, har - Aida Farida; Irawadi Jamaran; A. Aziz Darwis; Khaswar Syamsu; Yandra Arkeman (Forum Pasca Sarjana, 2011)
Financial and non-financial factors are important indicators to evaluate performance of corporation. The main objective of this study is to build a model for improving performance of estate and plant by using balance scorecard. The study uses balance scorecard, and fuzzy analytical hierarchy process to model the criteria of performance measurement for both estate and plant. Results generated from the model of estate performance criteria measurements are seed, fertilizing, cost management, harvest, plant maintenance, production, and employee development. Results generated from the model of plant performance criteria measurements are production rate, cost management, losses, plant utilization, CPO quality, employee development, and environmental friendly production process. Estate and plant scoring board model are used to measure the performance of estate and plant based on set targets. Results generated from estate scoring board model are low performance in cost management, production, and employed development. Results generated from plant scoring board model are low performance in cost management, losses, and environmental friendly production process. Performance improvement model for estate and plant are conducted by using expert management. The result generated from this study is a software of decision support system by using expert management, and it is called In-KK v1.00. Keywords: oil palm agroindustry, key performance indicator, scoring board